FACTOR AFFECTING THE IMPLEMENTATION OF CLASS MANAGEMENT EDUCATIONAL PROGRAM STUDENTS FIELD EXPERIENCE (PPLK) - 670-676 , An Nisaa Defi (CIVED, 2015)
ABSTRACT   This study aims to reveal the factors that can hinder the implementation of the program the student class management education experience with populations in this study were majoring in Civil Engineering who was been carrying out Educational Field Experience Program in half July-December 2014. The research is a quantitative descriptive. The sampling thecnique using simple random sampling as many as 39 of the population 64 people. Data were collected using a questionnaire with Likert Scale consisting of 4 possible answers. The number of statements in the questionnaire was 51 point statements. The result showed that the factors that can hinder the implementation class management Educational Program Students Field Experience is: (1) Physical environment with an average degree of achievement of 71,77% are sufficient. (2) Socio-emotional conditions with an average degree of achievement of 74,39% is categorized enough (3) Organizational conditions with an average degree of achievement of 63,78% are sufficient.. Keywords: PPLK Student, Class Management